(untitled) (Global Journal of Human-Social Science, 2021)
Traduzir novamente) This is article seeks to reflect the Pentecostalism in its original point of view, and to the extent that is thas become increasingly popular in recente times. In fact, the importance of this religious movement requires attention and if Assisi is Neo-pentecostalism, serving as a broad religious meaning, ctiha his faithful and is proposed as the espinal and political response to liberate Brazil fron the plagues that afflict it. This article seeks to reflect on how the process of the emergence of neopentecostalismo from pentecostalisme es pesetracko and solidification in the Brazil media and political society.